Pendampingan Peningkatan Kualitas Briket Arang Kulit Batang Sagu Untuk Standar Ekspor di Sentra Sagu Sungai Tohor Kabupaten Kepulauan Meranti - Hafidawati Hafidawati; Ida Zahrina; Mira Dharma; Vonny Setairies; Iwan Kurniawan; Hendro Ekwarso; Syarfi Daud (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Sago bark waste (uyung) is abundant in Sungai Tohor Village, Kepulauan Meranti Regency, but has not been optimally utilized, causing environmental problems. Research conducted by the Environmental Engineering Study Program, Universitas Riau, has developed charcoal briquettes from sago bark, which are then implemented in the community to provide real impacts on improving quality of life and supporting the impactful campus program. This community service aims to assist local communities and businesses in improving the quality of sago bark charcoal briquettes to meet export standards and support village energy transition. The methods included counseling, Focus Group Discussions (FGD), technical training on briquette production, quality testing, and business management strengthening. The FGD held in Selat Panjang (September 18–21, 2025) involved 20 participants from strategic partners including the Meranti Regency Department of Industry and Trade, Department of Housing and Environment, Sago Center, Village-Owned Enterprises (BUMDes), and export practitioners from Ecotohor Solution. The results showed increased community understanding of export briquette standards with characteristics such as high calorific value, low moisture content, good density, and stable combustion. This technology implementation strengthens the potential of sago bark charcoal briquettes as a village flagship product for the global market while promoting energy transition and sustainable economy.